Simultaneous Kidney Transplantation and Abdominoplasty in a Prune-Belly Syndrome Patient - Silva, André Barcelos da; Patavino, Guilherme Alonso Daud; Bonfitto, Miguel; Ferreira Aguiar, Wilson; Foresto, Renato Demarchi; Tedesco-Silva, Helio; Medina Pestana, José (Brazilian Journal of Transplantation, 2023)
Simultaneous correction of the abdominal wall defect during kidney transplantation in a patient with Prune-Belly Syndrome (PBS) was not described yet. The abdominoplasty is postponed because the concomitant approach would result in greater complexity to the procedure and increase the surgical risk. We report a 14-year-old male patient with PBS submitted to simultaneous kidney transplantation and abdominoplasty, describing the steps of the surgery. This approach is feasible and promotes functional improvement of the abdomen, minimizing potential damage and costs of future approaches, and provides a better quality of life.